1 - Researching Gender Relations in Africa: Directions and Landmarks in Feminist Research Methodology - Ahikire, Josephine (Journal of Higher Education in Africa, 2022)
This article is a reflection on critical perspectives on researching gender relations. It is an overview of the landmarks in feminist methodology and the quest for greater inventiveness and sensibility in researching gender relations in Africa. Critical questions include: What milestones have been reached and why? What flaws do we need to correct and what will it take? The article was generated as part of feminist research methodology training at CODESRIA. It is designed to be a contribution to the ongoing African feminist conversation around the critical need for debunking colonial discourses and developmentalist buzzwords in researching gender relations, and the need for African realities to inform research and knowledge generation on gender relations on the continent.